IMPACT OF GREEN ADVERTISING ON GREEN PURCHASE INTENTION OF SMARTPHONE USERS IN SOKOTO, NIGERIA - ZAILANI, BABANGIDA SALAU; MAHADI , FATIMA ABDULLAHI; ABDULLAHI, WASILATU GARBA; ABUBAKAR, ZINATU IDRIS (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
The advancement in environmental concern had influenced customer attitude, behavior, and lifestyle in purchasing telecommunication products and services. There is significant shift from utilizing telecommunication products to greener environment. These had pressured many Smartphone manufacturers to consider on refining the users repurchase intention strategy to focus more on green advertising to achieve customer retention. The impact of green advertising on the green purchase intention has been widely studied by previous literature in the organizational contexts. However, the empirical research from the customer perspective is rather limited. Therefore, this study proposed to fill in the green purchase intention literature gap by focusing on the relationship between green advertising and green purchase intention from the customer perspective using Usmanu Danfodio University Smartphone users. The study used descriptive survey research design consists of 24, 087 students of Usmanu Danfodio University Sokoto (UDUS), using Smartphone with a sample size of 379, out of the total population of UDUS students. Using PLS-SEM the study test the hypotheses formulated and the findings revealed that Product Knowledge has a higher influence on Green Purchase Intention with (β = 0.590), while Green Advertising has (β = 0.011) has the second influence to the Green Purchase Intention. While the moderation is positive and insignificant (β = 0.011). The study recommends that Smartphone marketers should be aware that student Smartphone consumers will make choices based on eco-labeling in the Smartphone, so obtaining appropriate eco-labels is a necessary to improve the business strategy for environmental enterprises.